Application of technology for the analysis of Small-Sided Games in football. From complexity to chaos in training design: Reference to number of players, playing space, orientation, time distribution, directionality with goalkeepers, and feedback - Asín-Izquierdo, I.; Gutiérrez-García, L.; Galiano C. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
Small-sided games (SSGs) are frequently used in football training programs and their design has been analyzed in scientific literature. The aim of this study was to analyze differences in the mechanical and physiological demands of football SSGs with various configurations over an effective time of 6 min through the application of GPS/GNSS technology, heart rate monitoring, and player self-perceived effort. Thirty football players (21.59 ± 4.35 years, 72.74 ± 9.01 kg, and 178.16 ± 0.93 cm) completed 138 recordings during MD-3 sessions (matchday-3, 76 h pre-match) using Catapult OptimEye S5 devices, synchronized with the Polar system. The training structure was similar for all measurements. Analyses and comparisons were made using a total of ten training tasks and six study variables (dimensions, orientation, number of players, directionality, time distribution, and coaches` feedback). SSGs played as 3 versus 3 showed higher mechanical responses with greater pitch sizes (p < 0.001) and without the presence of goalkeepers (p < 0.032). SSGs with a 6 versus 6 format showed higher velocities were attained when the pitch was long (p = 0.021) and when the duration of the set was shorter (i.e., 2 min; p < 0.015). SSGs arranged as 3 versus 3, showed superior results for internal and external variables in comparison with 6 versus 6 (p < 0.025). The application of new technology is necessary to understand internal and external workload responses to the multiple possible variations of the elements of SSGs. The understanding of these resources will contribute to the development of training tasks based on the complexity of football itself, considering the wide possibilities offered to coaches.